The Role of Protein–Lipid Interactions in Priming the Bacterial Translocon - Matt Sinclair; Emad Tajkhorshid (Membranes)
Protein–lipid interactions demonstrate important regulatory roles in the function of membrane proteins. Nevertheless, due to the semi-liquid nature and heterogeneity of biological membranes, and dissecting the details of such interactions at high resolutions continues to pose a major challenge to experimental biophysical techniques. Computational techniques such as molecular dynamics (MD) offer an alternative approach with both temporally and spatially high resolutions. Here, we present an extensive series of MD simulations focused on the inner membrane protein YidC (PDB: 6AL2) from Escherichia coli, a key insertase responsible for the integration and folding of membrane proteins. Notably, we observed rare lipid fenestration events, where lipids fully penetrate the vestibule of YidC, providing new insights into the lipid-mediated regulation of protein insertion mechanisms. Our findings highlight the direct involvement of lipids in modulating the greasy slide of YidC and suggest that lipids enhance the local flexibility of the C1 domain, which is crucial for recruiting substrate peptides. These results contribute to a deeper understanding of how protein–lipid interactions facilitate the functional dynamics of membrane protein insertases, with implications for broader studies of membrane protein biology.